Mechanical Engineering: Medium-Sized Companies with Highest Savings Potential - Alexander S. Kritikos; Alexander Schiersch (Weekly Report, 2010)
The German mechanical engineering industry, dominated by medium-sized companies, is greatly successful - both on the domestic and on the international market. A first analysis conducted by DIW Berlin reveals that this success cannot be attributed to a better exploitation of potential efficiencies - mechanical engineering is about as efficient as other key sectors (for instance the chemical industry). In fact, despite their obvious success medium-sized mechanical engineering businesses have larger savings potential than bigger companies and even than smaller enterprises in this industry.
Keywords: C40; L60; 330; Data envelopment analysis; German engineering firms; Efficiency; Firm size